(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective- The primary objective of this study was to determine the pattern of associated injuries along with the maxillofacial trauma. Methodology- Data collection was done retrospectively from the previous records of 10 years for patients affected with facial trauma along with associated injuries. Age, gender, cause, type of injury and fractures elsewhere in the body was also recorded. Results- Total out of 750 patients 110 patients were included in the study on meeting the inclusion and exclusion criteria. Most common associated injuries in maxillofacial trauma were head injury (51.82%) followed by orthopaedic injury (44.54%). Conclusion- Head is in close proximity and also the most prominent part to the maxillofacial region therefore it is most susceptible to injury along with maxillofacial injury.